Emergence and content of modern economic analysis - Fellner, William (New York, 1960)
The present volume has resulted from lecture notes for an under graduate course at Yale. This is two-s mester course in which I have been making an effort to give modern economic analysis a reasonably rounded presentation and, at the same time, to link contemporary theory to its historical antecedents. Author would like to put in a word for this method of acquainting students with the main content of contemporary economics.
Keywords: Economics